Case of a 56 year old female with long-standing resistant hypertension and referred at our cardiac centre for catheter-based radiofrequency renal denervation - Sen, Naresh; Park, Keum Soo (International Journal of Research in Medical Sciences, 2016)
A 56 -year-old female with long-standing resistant hypertension to treatment with a combination of seven different drugs, referred for catheter-based radiofrequency renal denervation (RDN). A radial access was chosen because the patient was very obese and of short stature. This described renal denervation through the radial artery might represent an alternative for patients in whom femoral access is a higher-risk option, such as very obese patients and patients with peripheral artery disease or with a higher bleeding risk. Nevertheless, with the current available system, this approach is difficult and cannot be widely used, not only because of the length but also because of the stiffness of the catheter.